(untitled) (Research, Society and Development, 2021)
The professor performs several functions at the university, an example of research, teaching and extension, and this can generate physical and mental overload. They must guide themselves and guide students towards a task to be performed, a value, a sense to seek, and, therefore, find the realization of life (self-realization) for themselves and their students. The aim of this study was, therefore, to reflect on the vocation / mission of the university professor’s work in the light of Logotherapy and Existential Analysis, proposing ways to deal with teaching-learning and the relationship with the student in the post-pandemic period. Bibliographic research in books and articles in databases was used. It was found that the teacher who finds his mission by exercising teaching and developing his creative values, even with all the objectives and overloads of physical and mental order, is capable of, in its noetic dimension, self-transcending and calling others to self-transcendence, acting as a driver that guides the meaning, mainly in the consequences that a reframing. In the post-pandemic there will be a new education, and the teacher and student must accept each other in the diverse demands that will result from this period, seeking more than a transmission of knowledge, but mainly an existential encounter.